An economic cost analysis of an expanding, multi-state behavioural telehealth intervention. (July 2019) - Yilmaz, Siobhan K; Horn, Brady P; Fore, Chris; Bonham, Caroline A
Introduction: In this paper the economic costs associated with a growing, multi-state telepsychiatry intervention serving rural American Indian/Alaska Native populations were compared to costs of travelling to provide/receive in-person treatment. Methods: Telepsychiatry costs were calculated using administrative, information-technology, equipment and technology components, and were compared to travel cost models. Both a patient travel and a psychiatrist travel model were estimated utilising ArcGIS software and unit costs gathered from literature and government sources. Cost structure and sensitivity analysis was also calculated by varying modeling parameters and assumptions. Results and Discussion: It is estimated that per-session costs were $93.90, $183.34, and $268.23 for telemedicine, provider-travel, and patient-travel, respectively. Restricting the analysis to satellite locations with a larger number of visits reduced telemedicine per-patient encounter costs (50 or more visits: $83.52; 100 or more visits: $80.41; and 150 or more visits: $76.25). The estimated cost efficiencies of telemedicine were more evident for highly rural communities. Finally, we found that a multi-state centre was cheaper than each state operating independently. Conclusions: Consistent with previous research, this study provides additional evidence of the economic efficiency associated with telemedicine interventions for rural American Indian/Alaska Native populations. Our results suggest that there are economies of scale in providing behavioural telemedicine and that bigger, multi-state telemedicine centres have lower overall costs compared to smaller, state-level centres. Additionally, results suggest that telemedicine structures with a higher number of per-satellite patient encounters have lower costs, and telemedicine centres delivering care to highly rural populations produce greater economic benefits.